Đáp án + Giải thích các bước giải:
Bài `14`: Tìm x, biết
a, `(x - 2)^2 + (y - 3)^2 = 0`
Vì `(x - 2)^2 \ge 0 ∀x`
`(y - 3)^2 \ge 0 ∀y`
`⇒ (x - 2)^2 + (y - 3)^2 \ge 0 ∀x,y`
Mà `(x - 2)^2 + (y - 3)^2 = 0`
`{((x - 2)^2 = 0),((y - 3)^2 = 0):} <=> {(x - 2 = 0),(y - 3 = 0):} <=> {(x = 0 + 2 = 2),(y = 0 + 3 = 3):}`
Vậy `x = 2 `
b, `5^( (x - 2) . (x + 3) ) = 1`
`5^ ( (x - 2) . (x + 3) ) = 5^0`
`=> (x - 2) . (x + 3) = 0`
⇒\(\left[ \begin{array}{l}x - 2 = 0\\x + 3 = 0\end{array} \right.\)
⇒\(\left[ \begin{array}{l}x = 0 + 2 = 2\\x = 0 - 3 = -3\end{array} \right.\)
Vậy `x \in {2 ; -3}`
c, `-(x - y)^2 = (yz - 3)^2`
`=> -(x - y)^2 - (yz - 3)^2 = 0`
`=> (x - y)^2 + (yz - 3)^2 = 0`
Vì `(x - y)^2 \ge 0`
`(yz - 3)^2 \ge 0`
`=> (x - y)^2 + (yz - 3)^2 \ge 0`
Mà `(x - y)^2 + (yz - 3)^2 = 0`
`{((x - y)^2 = 0),((yz - 3)^2 = 0):} <=> {(x - y = 0),(yz - 3 = 0):} <=> {(x = y),(y = 3/z):}`
Vậy `x = 3/z`